Current approaches to the formation of a comfortable urban environment - Generalova, Elena M.; Yudanova, Elizaveta A. (Arhitekton, 2025)
The article examines the issue of human interaction with the urban environment. Modern trends and concepts in the development of public urban spaces are systematized, taking into account their impact on the mental and physical state of a person. Using Samara as an example, an analysis of city streets with predominantly residential buildings from different periods is conducted. The study examines the development of a three-dimensional urban environment by creating above-ground and underground pedestrian systems connecting buildings and allowing comfortable movement around the city all year round, regardless of weather conditions.